Membrane domain organization of myelinated axons requires βII spectrin - Zhang, Chuansheng (The Rockefeller University Press, 2013)
The precise and remarkable subdivision of myelinated axons into molecularly and functionally distinct membrane domains depends on axoglial junctions that function as barriers. However, the molecular basis of these barriers remains poorly understood. Here, we report that genetic ablation and loss of axonal βII spectrin eradicated the paranodal barrier that normally separates juxtaparanodal K(+) channel protein complexes located beneath the myelin sheath from Na(+) channels located at nodes of Ranvier. Surprisingly, the K(+) channels and their associated proteins redistributed into paranodes where they colocalized with intact Caspr-labeled axoglial junctions. Furthermore, electron microscopic analysis of the junctions showed intact paranodal septate-like junctions. Thus, the paranodal spectrin-based submembranous cytoskeleton comprises the paranodal barriers required for myelinated axon domain organization.